(untitled) (Advances in Applied Mathematics and Mechanics, 2018)
In this research, motion and deformation of a red blood cell (RBC) in a microchannel with stenosis is investigated by combined Lattice Boltzmann-Immersed Boundary method. The fluid flow occurs due to the pressure difference between the inlet and the outlet of the microchannel. The immersed boundary algorithm guarantees that there is no relative velocity between the RBC and fluid. Therefore, mass transfer along the immersed border does not occur. It can be seen that the healthy RBC has more deformation and passes the stenosis more easily while the sick one passes the stenosis with less deformation and returns to its initial state faster. Increasing the pressure gradient (i.e., increasing Reynolds number) would cause more deformation of the RBC. It is found that a healthy RBC moves faster than a sick one along the microchannel. Blood pressure increases due to the presence of stenosis and low deformable RBCs. It is the reason of many serious diseases including cardiovascular diseases. The results of this paper were compared to the previous valid results and good agreements were observed.